MgO Effect on The Dielectric Properties of BaTiO3 - Boumous, S.; Belkhiat, S.; Kharchouche, F. (Engineering, Technology & Applied Science Research, 2019)
The dielectric properties of barium titanate as functions of the MgO addition in various rates are investigated in this paper. The ceramics were prepared by conventional methods. X-ray diffraction, scanning electron microscopy and energy dispersive spectrometry, were applied to determine the structure and microstructure of the studied material. Phases MgO, TiO and TiO2, have been detected. Decrease of the grain size with increasing MgO content was observed. Measurements of εr, tgδ and resistance have been performed at temperatures ranging from 300C to 4000C. The electric permittivity (εr) showed a considerable decrease with increasing MgO concentration. Additionally, for low MgO concentration (10£mol.% MgO) a shift of the dielectric loss peak (tgδm) towards low temperatures was observed. When the MgO content was ≥15mol.% MgO the tgδm moved into higher temperatures. The obtained results indicate that the substitution of Mg2+ ions in B-site ions (Ti4+) had a significant influence on the values of εr, tgδ and the resistance increase of the ceramics.